Implementation of machine learning algorithms using control-flow and dataflow paradigms - Milutinović, Veljko (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series., 2022)
"This is a reference book for experienced professionals, that treats four widely used data-mining algorithms in a novel way, offering a basic introduction with issues of importance, advantages and disadvantages of these algorithms"--